Aspectos teórico-construtivos do neoconstitucionalismo brasileiro e a relação com o Estado de Direito - Silva, Leandro Suriani da (2016)
This thesis reflects a sequence of studies involving neoconstitucionalism theories developed in Brazil and their criticism. It was demonstrated the construction of constitutionalism in Brazil and the reasons for the emergence of the institute called neoconstitutionalism, which introduced a new techniques for interpretation of the Constitution and conferred more freedom to court judges to introduce changes in social, economic and political issues in society, without the intervention of the Congress. At the same time, although recognized as a mechanism able to bring more effectiveness to law, we tried to present in this work the criticism inaugurated against this theory, especially about the risks in moving away persistently the laws issued by the Brazilian Congress, with prevalence of constitutional principles, leaving to the particularly criterion of court judges to settlement the cases, even more in a context of a democratic society, in which exists a real differences of opinions on various themes and issues